Revisiting the core EP inverse and its extension to rectangular matrices. Issue 2 (19th February 2018) - Ferreyra, D.E.; Levis, F.E.; Thome, N.
Abstract: In this paper, we revise the core EP inverse of a square matrix introduced by Prasad and Mohana in [12], Core EP inverse, Linear and Multilinear Algebra 62 (3) (2014), 792–802. Firstly, we give a new representation and a new characterization of the core EP inverse. Then, we study some properties of the core EP inverse by using a representation by block matrices. Secondly, we extend the notion of core EP inverse to rectangular matrices by means of a weighted core EP decomposition. Finally, we study some properties of weighted core EP inverses.